Examining child schooling/care location and child temperament as predictors of restaurant-related behaviors during the COVID-19 pandemic: findings from a nationally representative survey - Goldsmith, Juliana; Ferrante, Mackenzie J.; Tauriello, Sara; Epstein, Leonard H.; Leone, Lucia A.; Anzman-Frasca, Stephanie (Frontiers in Nutrition, 2024)
Purpose: Emerging research highlights impacts of the COVID-19 pandemic on U.S. families, including changes in eating behavior and increased child body mass index. Aims of the present study were to examine whether child temperament and at-home vs. out-of-home childcare/school predicted families' restaurant-related behaviors during the pandemic. Examining energy balancerelated behaviors, like restaurant patronage, during the pandemic can help better understand lasting impacts on child health behaviors and health outcomes.Methods: An online survey was administered to U.S. parents with a 4-to-8-year-old child in October 2020 (n=1000). Linear and logistic regression examined whether child temperament and at home vs. out-of-home childcare/school predicted: 1) the frequency the child consumed restaurant meals (take-out, delivery, dine-in), 2) who chose the child's restaurant meal, and 3) parent-reported reasons for the child's meal choice. Income, education, employment, race/ethnicity, and regional COVID-19 restrictions were tested as covariates.Results: Parents with children higher on negative affectivity reported more frequent restaurant use in-person (p<.05) and via delivery (p<.05) compared to parents of children lower on negativity. Child negativity was also linked with parent-reported reasons for children's restaurant meal choices. Parents of children receiving at-home childcare/schooling used delivery services less frequently than those receiving out-of-home care or schooling (p<0.01).Conclusions: These findings suggest that individual and family factors may impact restaurant use and the meal selection process for children using restaurants during and beyond the COVID-19 era. Continued examination of individual differences in the impacts of the COVID-19 pandemic can facilitate intervention and policy approaches that fit with different families' needs.